Utilization of an Eilat Virus-Based Chimera for Serological Detection of Chikungunya Infection. - Jesse H Erasmus; James Needham; Syamal Raychaudhuri; Michael S Diamond; David W C Beasley; Stan Morkowski; Henrik Salje; Ildefonso Fernandez Salas; Dal Young Kim; Ilya Frolov; Farooq Nasar; Scott C Weaver (Public Library of Science (PLoS), 2015)
In December of 2013, chikungunya virus (CHIKV), an alphavirus in the family Togaviridae, was introduced to the island of Saint Martin in the Caribbean, resulting in the first autochthonous cases reported in the Americas. As of January 2015, local and imported CHIKV has been reported in 50 American countries with over 1.1 million suspected cases. CHIKV causes a severe arthralgic disease for which there are no approved vaccines or therapeutics. Furthermore, the lack of a commercially available, sensitive, and affordable diagnostic assay limits surveillance and control efforts. To address this issue, we utilized an insect-specific alphavirus, Eilat virus (EILV), to develop a diagnostic antigen that does not require biosafety containment facilities to produce. We demonstrated that EILV/CHIKV replicates to high titers in insect cells and can be applied directly in enzyme-linked immunosorbent assays without inactivation, resulting in highly sensitive detection of recent and past CHIKV infection, and outperforming traditional antigen preparations.